Gold In-and-Out: A Toolkit for Analyzing Subcellular Distribution of Immunogold-Labeled Membrane Proteins in Freeze-Fracture Replica Images - Guerrero-Given, Debbie; Goldin, Seth L.; Thomas, Connon I.; Anthony, Skylar A.; Jerez, Diego; Kamasawa, Naomi (Frontiers in Neuroanatomy, 2022)
Integral membrane proteins such as ion channels, transporters, and receptors shape cell activity and mediate cell-to-cell communication in the brain. The distribution, quantity, and clustering arrangement of those proteins contributes to the physiological properties of the cell, therefore precise quantification of their state can be used to gain insight into cellular function. Using a highly sensitive immunoelectron microscopy technique called sodium dodecyl sulfate-digested freeze fracture replica immunogold labeling (SDS-FRL), multiple membrane proteins can be tagged with different sizes of immunogold particles at once and visualized two-dimensionally. For quantification, gold particles in the images must be annotated, then different mathematical and statistical methods must be applied to characterize the distribution states of proteins of interest. To perform such analyses in a user-friendly manner, we developed a program with a simple graphical user interface called Gold In-and-Out (GIO), which integrates several classical and novel analysis methods for immunogold labeled replicas into one self-contained package. GIO takes an input of particle coordinates, then allows users to implement analysis methods such as nearest neighbor distance and particle clustering. The program not only performs the selected analysis, but also automatically compares the results of the real distribution to a random distribution of the same number of particles on the membrane region of interest. In addition to classical approaches for analyzing the protein distribution, GIO includes new tools to analyze the positional bias of a target protein relative to a morphological landmark such as dendritic spines, and can also be applied for synaptic protein analysis. Gold Rippler provides a normalized metric of particle density that is resistant to differences in labeling efficiency among samples, while Gold Star is useful for quantifying distances between a protein and landmark. This package aims to help standardize analysis methods for subcellular and synaptic protein localization with a user-friendly interface while increasing the efficiency of these time-consuming analyses.